‘Tkw’ Sebuah Perangkap Perdagangan Perempuan (Menelisik Femonena Human Traffiking Di Kabupaten Sambas) - Atem Atem (PSGA LP2M IAIN Pontianak, 2017)
Human trafficking has become a global issue that caught attention of many countries and also this crime has been included as heavy violations of human rights. The Developing countries like Indonesia often become the targets of criminal practices-based on human trafficking. Diverse modes have done which is throught the distribution of labour abroad. Women and children are the most listed as victims of human trafficking with the exploitation purpose. The border area has become a transit point for the distribution of workforce is either legal or illegal so the border is become a vulnerable area of human trafficking practices. In west Kalimantan particularly in Sambas Regency, the current transitions of ilegal labour to Malaysia is an usual and they not aware has a victims of human trafficking. This study attempt to describe and analysis the phenomenon of trafficking in person with mode of lobor distribution especially the case infemale worker (TKW) in Sambas Regency throught qualitative approach of techniques of observation and interview limited and also literature review.